Analysis of Factors Affecting The Improvement of Financial Satisfaction of The Millennial Generation - Nurtati, Nurtati; Nagara, Patria; Yadewani, Dorris; Nazar, Nisrina (Universitas Bumigora, 2024)
Financial satisfaction is a crucial factor in achieving prosperity. However, the contemporary situation is that the millennial age is perceived as having difficulty reaching financial contentment. This research aims to analyze the factors that significantly influence the level of financial satisfaction of the millennial generation in Pariaman, Indonesia. The method used in this research is a quantitative approach with survey data collection methods. The collected data was then analyzed using multiple linear regression analysis. A total of 100 millennial generation respondents were involved in this research. The results show that financial behavior, and primary agents significantly and positively affect financial satisfaction. On the other hand, risk tolerance, financial self-efficacy, secondary agents, and consumer’s childhood experience do not significantly influence financial satisfaction. This study contributes in improving the understanding of the factors influencing the financial contentment of millennials. The findings make theoretical and managerial advances by assisting millennials in understanding the factors that influence their financial happiness. Furthermore, these findings serve as a foundation for future studies into other factors influencing financial contentment among millennials in Indonesia.